Formulasi Tablet Effervescent Ekstrak Kulit Buah Ddelima Putih (Punica granatum var. album) dengan Variasi Asam Sitrat dan Asam Tartrat - Rizqi Fajri Ramadhani; Andi Sri Suriati Amal; Fitria Susilowati (University Of Darussalam Gontor, 2018)
Allah created all the plants in this world with their own benefits. Pomegranate is one of the plants that has many benefits. One part of the pomegranate that can be utilized to be effervescent tablet is the fruit peel. One of the sources ingredients in the formulation of effervescent tablet is the source of acid. This study aims to find the best formula for effervescent tablets of extract leather White Pomegranate and investigating the effect of variation of citric and tartrate acid to characteristic of granule and tablet. The ratio of citric acid and tartare acid used was Formulation I (3: 2), Formulation II (2: 2), and Formulation III (4: 3). The method used was direct screw press method. The physical quality granule was tested including the flow time, angle of repose, and tap index. The physical quality of the effervescent tablet was tested including uniformity of weight, hardness, friability, and dissolving time. Analysis of the multiform statistics show that variations of citric and tartrate acid gives significant influence towards the angle of repose and hardness of the tablet, but no significant to the time of flow, tap index, uniformity of weight, friability, and dissolving time. The best formula was at the formulation III (citric acid: tartrate acid, 4:3).